Field notes contributed by multiple observers, summer 1989 - Thelen, Edet al; Hinshaw, Lindaet al; Neal, Tomet al; Hemesath, Lisaet al; Fraley, Clintet al; Jennings, Darrellet al (1989)
Summer report of birds and locations contributed by multiple observers. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1989. Epson - sheet feed/flatbed